Perry's Handbook Example 12-18 Video Solution - Hariri, M. Hossein (McGraw-Hill's AccessEngineering., 2011)
This video illustrates the procedure for preparing a psychrometric chart for dipropylene glycol. The example calculation uses the Clausius-Claperyon equation for vapor pressure. Results are presented as Fig 12-21.